Підвищення надійності пристроїв РПН силових трансформаторів - Хоменко, Ігор Васильович; Федосеєнко, Олена Миколаївна; Стасюк, Іван Володимирович (Український державний університет залізничного транспорту, 2017)
Встановлено, що одним із способів підвищення надійності роботи силового трансформатора є підвищення надійності роботи його пристрою регулювання під навантаженням (РПН). Наведено статистику відмов його окремих елементів, показано, що особливо ненадійними елементами пристрою РПН є привод і контактор. Для підвищення надійності розглядається можливість його розроблення на базі двигуна з ротором, що котиться (ДРК). Проведено критичний аналіз сучасних пристроїв РПН і пропонованого технічного рішення. На основі загальної теорії електромагнітного поля розроблено методику і алгоритм розрахунку нових типорозмірів ДРК для пристроїв РПН силових трансформаторів. Проведено аналіз експлуатаційної надійності пристроїв РПН на основі статистичних матеріалів, розраховані основні показники надійності його елементів. Показано перспективу розвитку нового пристрою РПН.

It is established that one of the effective ways to improve the reliability of the power transformer as a whole is to increase the reliability of its on-load tap-changer (OLTC). As a result of the analysis of statistical material obtained under real operating conditions (the number of transformers is 1000 pieces, the observation period is 4 years), the failure statistics of its individual elements are given. It is shown that the most not reliable elements of the OLTC are the drive and the contactor. To improve the reliability of the OLTC, the possibility of its development on the basis of an engine with a rolling rotor is considered. A critical analysis of modern OLTC and the proposed technical solution is carried out. The technical and economic feasibility of developing and implementing a new device has been established. On the basis of the general theory of the electromagnetic field, a technique and an algorithm for calculating new sizes of an engine with a rolling rotor for OLTC of power transformers has been developed. The analysis of operational reliability of OLTC based on statistical materials is carried out; the main reliability indices of its elements are calculated. It is established that the introduction of a new technical solution will increase the reliability of the OLTC by 25% and the power transformer by 2-4%. The perspective of the development of a new OLTC device is presented.
Improving the reliability of power transformers OLTC devices
Keywords: трансформаторне обладнання; електрична мережа; регулювання напруги; електродвигуни; електромагнітні процеси; power transformer; on-load tap-changer; motor with rolling rotor; operational reliability